CHANGE IN THE SENSITIVITY OF THE THERMANOEMOMETRIC BIOFUEL FLOWMETER - Ільченко, Андрій (SWorldJournal, 2024)
The paper examines the process of changing the sensitivity of the thermo-anemometric biofuel flow meter depending on the fuel consumption, the distance between the heater and the heat converters. It is shown that in order to improve the sensitivity of the